Cleopatra in space. Book two, The thief and the sword - Maihack, Mike (Maihack, Mike. Cleopatra in space, 2015)
"A mysterious thief has stolen the ancient sword Cleo recovered in book one: Target practice, and she's determined to get it back. But her teachers at Yasiro Academy forbid her from risking her life, so she's stuck at school, trying to adjust to her newfound popularity and responsibility. And when she learns more about the prophecy that names her the savior of the galaxy, she must go on a dangerous journey to find the time tablets that could decide her fate-- before they fall into the wrong hands."